Philosophical reflection drawn from the experience of the design weaknesses of PhD students through research activities - Bruce, Bemena; Aurélien, JERSON; André, TOTOHASINA; Daniel Rajaonasy, FENO; -, ARMAND (Lembaga Sembilan Tiga Community, 2025)
The productivity generated by doctoral research activities requires exclusively laborious work in order to have yields with all the qualities practically satisfactory for these tasks. The implementation of the state of the art and the construction of a